Grafične tehnike pri pouku likovne vzgoje v drugem razredu osnovne šole - Mlinarič, Dragica (Revija za elementarno izobraževanje, 2009)
Graphic techniques in art lessons in the second grade of elementary school. The article describes the findings based on a case study. We have observed analyzed and evaluated activities in the classroom during art lessons, where the focus was set on graphic techniques: monotype, collage print, seal printing, collagraphy and computer graphics. The findings show that the pupils were the most independent and with the highest motivation while working on the collage technique, while on the other side the least motivational was seal printing. The pupils were more or less skillful at other graphic techniques. The findings also show that the pupil’s interest in learning terms about graphic arts and his/her positive attitude towards graphic techniques increased with the number of performed lessons. We found out that the material conditions are on a satisfactory level. Considering the pupils’ interest, graphic arts as a particular area of arts, is more or less in the same position as other areas. Nevertheless, the most attractive for the pupils is computer graphics. We also noticed that pupils were highly motivated while carrying out the graphic activities and do not want to miss them in the future.